2008
DOI: 10.1093/europace/eun283
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology study and radiofrequency catheter ablation of atriofascicular tracts with decremental properties (Mahaim fibre) at the tricuspid annulus

Abstract: Mahaim fibre is commonly located between 8 and 10 o'clock at tricuspid annulus. M potential guides to successful RF ablation in most patients. Mahaim junctional acceleration is commonly seen during RF ablation guided by M potential map.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The ventricular termination of a Mahaim fiber can be identified through activation mapping, but because of the tendency to have a wide insertion in the ventricle, ablation at its ventricular breakout is less likely to be successful. Therefore, a Maham fiber must be located through identification of Mahaim potentials, either on the atrial side of the right atrioventricular groove or along the course of the Mahaim fiber as it courses beneath the endocardial surface of the right ventricle toward the apex 1, 2, 3, 4…”
Section: Discussionmentioning
confidence: 99%
“…The ventricular termination of a Mahaim fiber can be identified through activation mapping, but because of the tendency to have a wide insertion in the ventricle, ablation at its ventricular breakout is less likely to be successful. Therefore, a Maham fiber must be located through identification of Mahaim potentials, either on the atrial side of the right atrioventricular groove or along the course of the Mahaim fiber as it courses beneath the endocardial surface of the right ventricle toward the apex 1, 2, 3, 4…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, a His-bundle potential can be seen (iii, red arrowheads): conduction through the MF has been abolished -for now, at least -and the normal conduction system has taken over. around the tricuspid annulus [12]. If nothing can be found, other MF pathways, or even other types of accessory pathways, must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Tachycardias with a QRS morphology and LBBB or left axis deviation pattern lead to antidromic atrioventricular reentrant tachycardia . Although MAP can often be seen in a structurally normal heart, it can also be accompanied by Ebstein's anomaly, additional accessory AV pathways (Kent), and AVNRT , . In their study of 15 Mahaim patients aged 12–44, Bohora et al reported preexcitation during normal sinus rhythm in six patients and Ebstein's anomaly on the echocardiogram in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the mechanism and site of origin of the Mahaim tachycardia was performed using standard pacing protocols and mapping methods. The criteria for the presence of MAP included the following: (1) Initial presence of preexcitation with normal QRS or LBBB morphology on the 12‐lead ECG. (2) Progressive lengthening of the AV interval and shortening of the His-ventricular (HV) interval during the short pacing cycle of preexcitation provoked with programmed atrial pacing. (3) Absence of retrograde conduction in the accessory pathway during ventricular stimulation. (4) Presence of right bundle branch electrogram preceding His bundle activation during anterograde preexcitation and SVT. …”
Section: Electrophysiology Studymentioning
confidence: 99%